Price competition model in decentralized and centralized supply chains with demand disruption - Chai Wenlong; Sun Huijun; Wang Wei; Wu Jianjun (Journal of Industrial Engineering and Management (JIEM), 2013)
Purpose: The paper studies the price competition of a supply chain with one supplier and two competing retailers under occasional demand disruption. Design/methodology/approach: The supply chain is either decentralized or centralized. The demand disruption for two retailers occurs with different probability. We analyze the effect of occurrence probability of demand disruption on the optimal prices of the supplier and two retailers. Findings: We find that the profits of supplier, retailers and supply chain are decreasing with the occurrence probability of demand disruption. Originality/value: It is helpful for supply chain members to adjust the original contracts to demand disruption.
Keywords: 650; Demand disruption; probability; price competition; profit